Application of Cognitive-behavioural Techniques on Changes in the Scope of Dieting Self-efficacy Level among Obese People - Malgorzata OBARA-GOLEBIOWSKA (Tehran University of Medical Sciences, 2017)
Please provide alternate text for this image to ensure accessibility for users with text-only browsers or assistive devices.